Case Report: Ventricular preexcitation-induced dilated cardiomyopathy improved by the pharmacologic suppression of ventricular preexcitation in three infants, and literature review - Chencheng, Dai; Min, Zhong; Wanming, Shi; Wen, Shangguan; Baojing, Guo; Yanyan, Xiao; Ling, Han; Deyong, Long (Frontiers in Pediatrics, 2024)
The therapy of ventricular preexcitation induced dilated cardiomyopathy in very small infants or infants with high risk of ablation is tough and related articles are rare.Effective pharmacotherapy to suppress the ventricular preexcitation is valuable. Aims:To evaluate the effectiveness and safety of pharmacotherapy for cardiac resynchronization in infants with ventricular preexcitation induced dilated cardiomyopathy. Methods and Results: 3 infants with ventricular preexcitation induced dilated cardiomyopathy, due to the disappearance of ventricular preexcitation during the placement of catheter,intermittent WPW pattern and right midseptal accessory pathway respectively, had received pharmacotherapy for cardiac resynchronization.The initial dosage of oral amiodarone was 5mg/kg.d and it was followed by the maintenance dosage of  2~2.5mg/kg.d 4 weeks later. Propafenone(15mg/kg.d) served as a supplement since amiodarone was not adequate in case 3. The 3 infants achieved successful pharmacologic suppression of ventricular preexcitation 10,6.5,4.5 weeks after the initiation of amiodarone respectively.They all got normalized contraction of interventricular septum and LVEF as well as reduced LVEDD gradually after the disappearance of ventricular preexcitation. No side effects associated with pharmacotherapy happened during the follow-up. Amiodarone had been withdrawed for 2 years and 5 months in Case 1 and 2.They both kept free from ventricular preexcitation and remained normal LVEF and LVEDD. Conclusions: Pharmacotherapy for cardiac resynchronization with oral amiodarone or combination with propafenone for infants with ventricular preexcitation induced dilated cardiomyopathy is effective and safe. Pharmacotherapy for cardiac resynchronization served as another therapeutic choice besides ablation.